Students’ Learning Engagement in the Topic of Atomic Concepts and the Periodic Table - Febriyani, Roseana; Erlina; Mayasari, Eni (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Learning engagement constitutes a critical component in the educational process, significantly influencing both the effectiveness of instruction and student academic achievement. This study aims to analyze the learning engagement of undergraduate students enrolled in a Chemistry Education program, specifically concerning their engagement with the subject matter of atomic concepts and the periodic system within the context of a general chemistry course. This research adopts a qualitative descriptive approach. Data were obtained through classroom observations, semi-structured interviews, and document analysis. Observational data were collected from a cohort of 31 students participating in lecture sessions. Based on the initial observational findings, 15 students were purposively selected for in-depth interviews, representing three distinct engagement profiles: highly engaged, moderately engaged, and minimally engaged. The results indicate that students’ behavioral, emotional, and cognitive engagement levels vary across categories. Behavioral engagement was predominantly classified as "high," with students demonstrating active participation in learning activities. Emotional engagement was categorized as "moderate," reflecting students’ interest in the subject matter, albeit with varying degrees of emotional involvement. Cognitive engagement was also categorized as "moderate," as most students exhibited cognitive involvement in line with the key indicators, although not consistently at an optimal level. In conclusion, while students generally demonstrated positive behavioral engagement, there remains room for improvement in fostering deeper emotional and cognitive engagement in learning about atomic concepts and the periodic system. These findings underscore the need for instructional strategies that holistically support all dimensions of student engagement to enhance learning outcomes in chemistry education.